The folding pathway of the genomic hepatitis delta virus ribozyme is dominated by slow folding of the pseudoknots - Chadalavada, Durga M; Senchak, Susan E; Bevilacqua, Philip C (Journal of molecular biology, 2002)
Hepatitis delta virus (HDV) replicates by a double rolling-circle mechanism that requires self-cleavage by closely related genomic and antigenomic versions of a ribozyme. We have previously shown that the uncleaved genomic ribozyme is subject to a variety of alternative (Alt) pairings. Sequence upstream of the ribozyme can regulate self-cleavage activity by formation of an Alt 1 ribozyme-containing structure that severely inhibits self-cleavage, or a P(-1) self-structure that permits rapid self-cleavage. Here, we test three other alternative pairings: Alt P1, Alt 2, and Alt 3. Alt P1 and Alt 3 contain primarily ribozyme-ribozyme interactions, while Alt 2 involves ribozyme-flanking sequence interaction. A number of single and double mutant ribozymes were prepared to increase or decrease the stability of the alternative pairings, and rates of self-cleavage were determined. Results of these experiments were consistent with the existence of the proposed alternative pairings and their ability to inhibit the overall rate of native ribozyme folding. Local misfolds are treated as internal equilibrium constants in a binding polynomial that modulates the intrinsic rate of cleavage. This model of equilibrium effects of misfolds should be general and apply to other ribozymes. All of the alternative pairings sequester a pseudoknot-forming strand. Folding of ribozymes containing Alt P1 and Alt 2 was accelerated by urea as long as the native ribozyme fold was sufficiently stable, while folding of mutants in which both of these alternative pairings had been removed were not stimulated by urea. This behavior suggests that the pseudoknots form by capture of an unfolded or appropriately rearranged alternative pairing by its complementary native strand. Fast-folding mutants were prepared by either weakening alternative pairings or by strengthening native pairings. A kinetic model was developed that accommodates these features and explains the position of the rate-limiting step for the G11C mutant. Implications of these results for structural and dynamic studies of the uncleaved HDV ribozyme are discussed.